Health insurance satisfaction, financial burden, locus of control and quality of life of cancer patients: a moderated mediation model. Issue 4 (22nd January 2021) - Pahlevan Sharif, Saeed; Naghavi, Navaz; Ong, Fon Sim; Sharif Nia, Hamid; Waheed, Hassam
Abstract : Purpose: The purpose of this paper is to examine the relationship between consumers' satisfaction with their health insurance and quality of life (QoL), the mediating role of perceived financial burden in this relationship, as well as the moderating effect of external locus of control (LoC) on the relationship between perceived financial burden and QoL among cancer patients. Design/methodology/approach: A cross-sectional design was employed in order to collect quantitative data by means of a self-administrated questionnaire. Participants consisted of 387 conveniently selected consumers diagnosed with cancer in Iran. Furthermore, the questionnaire was translated into Persian using a forward–backward method. The model was tested using partial least squares structural equation modeling (PLS-SEM). Findings: The results indicate that the more satisfied patients are with their health insurance, the higher QoL they experience, and this relationship is explained through reducing perceived financial burden in terms of direct and indirect costs of the disease. Although external LoC belief is negatively related to QoL, it buffers the negative association between financial burden and QoL. Practical implications: Reducing the disparity between consumers' expectation and perception of the comprehensiveness of health insurance policies may relieve consumers' anxiety stemming from financial worries. Originality/value: This paper fills a gap in the literature where consumers' perception about quality of insurance and its relationship with their QoL has received little attention so far.